1 - Développement agricole et indépendance alimentaire - BOURENANE, Nacer (Africa Development, 1983)
The major argument of this article is thai the agricultural model propounded to the Third World countries had not been that successful when applied in the developed capitalist countries. In fact, that model even creates dangers for those Third World countries, among which these are the main ones: Dependency to foreign technology and capital. Risks on the environment. The «psychosis» of the powers of the under-developed countries triggered by the fear of famine very often leads them to adopt one of these two lines of development without much reflection and critical analysis: To take for granted projects of «agrarian or rural development» launched by international ami foreign institutions (public or private). To launch out agricultural development projects without first defining middle and long terms priorities. In both cases, although the approach and results can be different, there is a constant: food self-sufficiency is not reached, and it is far from being reached (see the example of India). But the author of this article prefers putting the emphasis of his study on the level of efficiency of the models propounded and their impli cations on the under-developed economies, taking as a starting-point the examples of the industrialised countries: technical effects, socio-political and economic consequences. The results are rather alarming: disappea rance of traditional know-how and techniques, massive resort to chemical fertilizers, growing food dependency, decline of the active agricultural population, regrouping of exploitable land, proletarianization, rural exodus, bigger gap between the poorest social classes and the state power hence accrued violence from each fraction... etc... all this being of course «un easily reversible». The author goes on with an enumeration of the consequences of the adoption of that development model on the lifestyles and incomes of the concerned populations. With the help of statistics and short case studies, he analyses the prospects of these models to agricultural producers and concludes by posing: can't we consider the export of such a model of agricultural development from the developed capitalist countries towards the Third World countries just as a mere means of consolidating their grip on our economies and securing their profits?